Previdência social como estratégia de fortalecimento da agricultura familiar no espaço rural do agreste central sergipano - Menezes, Júnio Andrade (2022)
The rural space in Brazil presents dynamic and heterogeneous relations, with family farmers being the most prominent social actors. The respective actors are often at the mercy of precarious public or private policies to access social rights. In this context, the social actors that nowadays are classified as family farmers spent half a century segregated from a fair a fair and democratic social security system in the country. Based on that, the present work sought to reflect under the empirical-analytical bias, the effects of social security for the agricultural production by the family farmers in the rural area of Agreste Central Sergipano. The methodological procedures involved theoretical reflections and surveys of secondary data through the Brazilian Institute of Geography and Statistics (IBGE) and the National Institute of Social Security (INSS) and fieldwork. In 2020, there were just over 9.6 social actors with active social security benefits in Brazil, more than half of them female. Currently, family farmers account for approximately 30% of the existing benefits in the Brazilian social security system. The Northeast of the country is the spatial area with the highest percentage of family farmers with INSS benefits. In the state of Sergipe, 211,319 pensions were active in April 2021 and of these, 53.3% were rural. The INSS agency in the rural space of the Agreste Central of Sergipe has the highest percentage of rural benefits in the state, and it is the second in financial amounts. Rural social security is not income from agricultural production, but is the result of years of work on the land. Thus, it is not a welfare or government policy, but a constitutional and institutionalized social right. This social insurance dissipates several socioeconomic improvements individually and collectively in the rural area of Agreste Central Sergipano. The delay in analyzing the requirements, bureaucracy, demands outside the productive reality of some family farmers, judicialization and dismantling of the INSS by neoliberal measures adopted by the current government, are some of the institutional and social obstacles that make it difficult for family farmers to access the Brazilian Rural Social Security System.